CAMEL Ratings and Bank Financial Distress Risk: Evidence from 2019–2023 - Hayati, Muhamad Fajrin; Blongkod, Harun; Mahmud, Muliyani (E-Jurnal Akuntansi; Vol 35 No 5 (2025), 2025)
This study investigates how CAMEL indicators influence financial distress among banks listed on the Indonesia Stock Exchange from 2019 to 2023. Employing a quantitative design, we estimate a structural equation model with AMOS 24 and supplement it with linear regression to trace the directional effects of each variable. A purposive sample of 40 banks forms the basis of the analysis. The findings reveal that the Capital Adequacy Ratio exerts a positive association with financial distress, whereas both Non-Performing Loans and the Net Profit Margin exhibit negative associations. Operating Expenses to Operating Income and the Loan-to-Deposit Ratio each display positive associations with distress risk. Taken together, the evidence suggests that CAMEL indicators alone do not exhaustively capture the onset of financial distress; additional, possibly more salient factors are likely at work. Keywords: CAMEL Analysis; Financial Distress; Bank.